Stroke and Bleeding in Atrial Fibrillation with Chronic Kidney Disease - Olesen, Jonas Bjerring; Lip, Gregory Y.H; Kamper, Anne-Lise; Hommel, Kristine; Køber, Lars; Lane, Deirdre A; Lindhardsen, Jesper; Gislason, Gunnar Hilmar; Torp-Pedersen, Christian (The New England journal of medicine, 2012)
Chronic Kidney Disease in Atrial Fibrillation In a study of data from Danish national registries, CKD was associated with an increased risk of stroke and bleeding among patients with atrial fibrillation. Warfarin decreased the risk of stroke among such patients. Both warfarin and aspirin increased the risk of bleeding. The prevalence of both atrial fibrillation and chronic kidney disease increases with age. 1 , 2 The prevalence of atrial fibrillation is 2.3% among persons 40 years of age or older and 5.9% among those 65 years of age or older, 2 and the prevalence of end-stage renal disease increases from approximately 3.5% among persons 45 to 64 years of age to nearly 6% among those 75 years of age or older. 1 Many patients have both disorders, 3 – 6 and the number of such patients is increasing, owing in part to the aging population and the improved survival in both diseases. Atrial fibrillation increases . . .